NARRATIVE STRUCTURE ANALYZED IN PANJO PATERSON’S STORY WRITING - Karo Sekali, Tria Novita Br; Sembiring, Rifky Sultan Nico; Sopha, Diana (PHILOLOGY Journal of English Language and Literature, 2024)
The purpose of this research is to find out what narrative text structures are contained in the short stories by Banjo Paterson entitled The Cat, Victor Second, Sitting in Judgment, Concerning a Dog - Fight, and Thirsty Island. The method used in this research is a qualitative method with a descriptive type. The results of this research show that the five story writing titles each have 5 narrative text structures in the form of abstract, orientation, evaluation, resolution and coda. If taken in total, there are 25 narrative text structures from the 5 story writing titles by Banjo Paterson.